Patterns and outcomes of cardiovascular emergency department encounters for men and women in the USA. (3rd October 2022) - Kobo, O; Raisi-Estabragh, Z; Elbadawi, A; Velagapudi, P; Sharma, G; Petersen, S E; Roguin, A; Mamas, M A
Abstract: Aims: We described sex-differential disease patterns and outcomes of over 20.6 million cardiovascular emergency department (ED) encounters in the USA. Methods and results: We analysed primary cardiovascular encounters from the Nationwide Emergency Department Sample (between 2016–2018). We grouped the documented cardiovascular diagnoses into 15 disease categories. The sample included 48.7% women; average age was 67 [54, 78] years. Men had greater overall baseline co-morbidity burden; however, women had higher rates of obesity, hypertension, and cerebrovascular disease. For women, the most common ED encounters were essential hypertension (16.0%), hypertensive heart or kidney disease (14.1%), and atrial fibrillation (AF)/flutter (10.2%). For men, the most common encounters were hypertensive heart or kidney disease (14.7%), essential hypertension (10.8%), and acute myocardial infarction (AMI, 10.7%). Women were more likely to present with essential hypertension, hypertensive crisis, AF/flutter, supraventricular tachycardia, pulmonary embolism, or ischaemic stroke. Men were more likely to present with AMI or cardiac arrest. In logistic regression models adjusted for baseline covariates, women with intracranial haemorrhage had higher risk of hospitalisation and death. Women with ischaemic stroke had higher risk of hospitalisation and death in ED. Women presenting with pulmonary embolism were less likely to be hospitalised but were more likely to die. Women with aortic aneurysm/dissection had higher risk of hospitalisation and death. Men were more likely to die following presentations with hypertensive heart or kidney disease, AF/flutter, AMI, or cardiac arrest. Conclusion: In this large nationally representative sample of cardiovascular ED presentations, we demonstrate significant sex differences in disease distribution, hospitalisation, and death. Funding Acknowledgement: Type of funding sources: None.